Data and Protocol for the Oxford Achieving Resilience During COVID-19 (ARC) Study. (24th March 2022) - Parsons, Sam; Todorovic, Ana; Lim, Michele C.; Songco, Annabel; Fox, Elaine
The Oxford Achieving Resilience during COVID-19 (ARC) study collected data from adolescents (aged 13–18), and parents of adolescents, from March 2020 to August 2021. Following a baseline survey (1274 completed baseline), participants were invited to 11 follow-up weekly surveys then 9 monthly follow-up surveys, and to an optional cognitive task. Each survey included questionnaires on mental health, resilience and wellbeing, COVID-19 related experiences and pandemic anxiety. Data is stored on the Open Science Framework ( https://osf.io/4b85w/ ), with comprehensive documentation on all measures. These data may be valuable to adolescent mental health researchers for further analyses and aggregation with other datasets.